2022
DOI: 10.3390/pathogens11050544
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Markers Correlate with the Progression of Active Tuberculosis Relative to Latent Control of Mycobacterium tuberculosis Infection in Macaques

Abstract: Despite a century of research into tuberculosis (TB), there is a dearth of reproducible, easily quantifiable, biomarkers that can predict disease onset and differentiate between host disease states. Due to the challenges associated with human sampling, nonhuman primates (NHPs) are utilized for recapitulating the closest possible modelling of human TB. To establish a predictive peripheral biomarker profile based on a larger cohort of rhesus macaques (RM), we analyzed results pertaining to peripheral blood serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The ATB and Mtb /SIV groups exhibited strong, positive correlations to their respective bacterial loads ( Table 2 ). These results support CRP at peak and endpoint as a correlate of more severe Mtb infection, with previous studies also suggesting that serum A/G ratio may be a viable biomarker of ATB ( 24 ), but similar to CRP, other confounding factors could interfere ( 37 ) and convolute the interpretation of results.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The ATB and Mtb /SIV groups exhibited strong, positive correlations to their respective bacterial loads ( Table 2 ). These results support CRP at peak and endpoint as a correlate of more severe Mtb infection, with previous studies also suggesting that serum A/G ratio may be a viable biomarker of ATB ( 24 ), but similar to CRP, other confounding factors could interfere ( 37 ) and convolute the interpretation of results.…”
Section: Resultssupporting
confidence: 87%
“…Bacterial burden, viral load, and immunologic response were determinants for classification to either active (ATB, n=16), latent (LTBI, n=11), Mtb /SIV co-infected ( Mtb /SIV, n=8), and naïve control (CTRL, n=6) groups. Through the use of serum chemistry, CRP values, and Albumin/Globulin (A/G) ratios were obtained ( 24 ). Blood cell percentages for monocytes, lymphocytes, and neutrophils were also quantified.…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35] The degree to which vaccines or anti-viral therapeutics might protect the lung from viral injury in an NHP model could be assessed using this pulmonary physiology testing protocol. In addition, many other fields of pulmonary research using NHP or other animal models may benefit from this protocol including research in the fields of tuberculosis, 36 asthma, 37 and inhaled pollutants. 10…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 125 Since this study, several other groups have confirmed the link between IDO activity and tuberculosis diagnosis or severity. 106 , 107 , 109 , 110 , 126 In addition, IDO1 may have diagnostic value in the early identification of multidrug-resistant (MDR) TB patients, as IDO1 has been positively correlated with cavitary lung lesions in TB patients, potentially indicating a more severe infectious state and a higher risk of developing MDR-TB. 111 These studies were also validated by metabolomics analysis, which showed that increased IDO activity helps to distinguish TB patients from healthy individuals.…”
Section: The [Kynurenine]/[tryptophan] Ratio In Respiratory Diseasesmentioning
confidence: 99%